Heterosis Exploitation in Brinjal against Fruit Borer Infestation under Semi-arid Climates of Gujarat: HETEROSIS AGAINST FRUIT BORER INFESTATION IN BRINJAL - Dhruv Pankaj Joshi; Patel, Nitin B; Joshi, Abhaben Mukeshkumar (Annals of Arid Zone, 2024)
Brinjal (Solanum melongena L.) suffers severe losses due to devastating and multi-insecticide resistant pest known as shoot and fruit borer (Leucinodes orbonalis Guenee). Breeding varieties against pest resistance is imperative. Hence, hybrids were developed for insect resistance. These insect-resistant hybrids were evaluated at multiple locations in Gujarat during late rabi 2021-22 in RBD, in order to analyse the heterosis of eight lines, six testers, their resulting 48 hybrids, and two standard checks for fruit borer infestation. Significant differences due to environment, genotypes, parents, hybrids, parents vs hybrids suggested the existence of genetic variation and overall heterosis. Overall, ABSR-2 × GAB-6 hybrid showed better performance against shoot and fruit borer resistance and was high in fruit yield in Gujarat’s semi-arid regions. It showed desirable heterobeltiosis and standard heterosis at multi-locations for fruit yield plant-1 compared to the standard checks.